Evaluation of the antibacterial potential of mango (Mangifera indica) seed kernels in Bangladesh - Sadiea, Rahila Zannat; Mozumder, Anandha; Mou, Moslema Jahan; Hasan, SM Nazmul; Sikder, Chandan; Akter, Sharmin; Saha, Biplob Kumar; Saha, Sukumar; Xue, Mengzhou; Wang, Huiqing; Zheng, Chunfu; Hossain, Md. Golzar (Frontiers in Tropical Diseases, 2024)
Antimicrobial resistance is a global threat. On the other hand, Bangladesh produces high-quality mangoes, yet the mango coat and seed kernel, which contain medicinal components, remain unused. Therefore, this study investigated the antibacterial potential and toxicity of ethanol extracts from mango (Mangifera indica) seed kernels, which specifically target the bacterial strains Staphylococcus aureus, Bacillus cereus, Escherichia coli, and Klebsiella sp. Amrapali variant mango seeds were collected, dried, ground into a fine powder, and extracted with ethanol at various ratios. The efficacy of the crude extract was tested via the disc diffusion method. The results demonstrated significant antibacterial activity against gram-positive bacteria (S. aureus and B. cereus), with clear zones of inhibition observed, especially in a dose-dependent manner. The pure crude extract inhibited the growth of S. aureus with a zone of 23 mm, identical to that produced by doxycycline. However, the extract exhibited limited activity against gram-negative bacteria (E. coli and Klebsiella sp.). Additionally, the extract was effective against multidrug-resistant S. aureus. The pure crude extract produced a 22.5 mm zone of inhibition against multidrug-resistant S. aureus, which was slightly smaller than that of gentamicin (23 mm) but larger than those of chloramphenicol (21 mm), vancomycin (20 mm), and tetracycline (16 mm). In vivo toxicity was assessed in mice, revealing no significant adverse effects on the hepatic structure or renal cortex at lower doses (100 μl of pure crude extract). However, higher doses caused mild histopathological changes in the liver and kidneys. These findings suggest that mango seed kernel extract holds promise as an alternative antibacterial agent, particularly against gram-positive and antibiotic-resistant bacteria, while being relatively safe at lower doses. Further research is needed to elucidate the active compounds, mechanisms of action, and broader applications of this extract in combating antibiotic-resistant bacterial infections.